Pelatihan Pemasaran Digital dan E-Commerce Bagi Mahasiwa Universitas Wijaya Kusuma dari Luar Jawa - Ariyani, Elfira Dwi; Tifania, Made Dwi Lysya; Nurrrachmatika, Salsabilla; Guterres, Ephivani Ashy; Nesimnasi, Soviana Nelci; Maslihah (PENITI BANGSA (Pemanfaatan Ilmu Pengetahuan dan Teknologi bagi Masyarakat), 2025)
Students of Universitas Wijaya Kusuma Surabaya (UWKS) from outside Java, particularly those from remote areas, often face difficulties in marketing their products online. Key challenges include limited access to information, low digital marketing and e-commerce literacy, inadequate technological infrastructure, and insufficient capital to develop online businesses. This community service program aims to enhance students’ knowledge and skills in digital marketing through training that combines education, discussion, and hands-on practice. Participants learned digital marketing concepts, product marketing strategies, and practiced creating and managing business accounts on the Shopee e-commerce platform. The results indicate an improvement in students’ ability to market products online, a stronger understanding of digital marketing strategies, and increased entrepreneurial motivation and potential. This program also supports wider market access for students from outside Java and promotes the equitable development of digital business across regions.